1998
DOI: 10.1159/000026478
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide, Free Radicals and Polyamines May Have a Role in the Membrane Pathology of Schizophrenia

Abstract: Studies on skin fibroblasts in culture derived from schizophrenic and control subjects showed that polyamines are increased, nitrate levels are reduced and thiobarbituric acid reacting substances did not alter in cultured cells from schizophrenic patients compared to control subjects. Results seem to indicate some alteration in membrane functions in schizophrenia, which is susceptible to neuroleptic treatment. Significantly increased levels of polyamines in drug-treated schizophrenic cells indicates a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Biochemical results also endorse the implication of NO in schizophrenia. In particular, low quantities of NO metabolites were noticed in plasma [ 33 , 34 , 35 ] and serum of first-episode, drug-naïve schizophrenics [ 36 , 37 , 38 ]. Bearing in mind that cognitive deficits is a typical feature of schizophrenics, lowering NO levels might indeed has severe repercussions for patients suffering from schizophrenia [ 27 ].…”
Section: No and Schizophreniamentioning
confidence: 99%
“…Biochemical results also endorse the implication of NO in schizophrenia. In particular, low quantities of NO metabolites were noticed in plasma [ 33 , 34 , 35 ] and serum of first-episode, drug-naïve schizophrenics [ 36 , 37 , 38 ]. Bearing in mind that cognitive deficits is a typical feature of schizophrenics, lowering NO levels might indeed has severe repercussions for patients suffering from schizophrenia [ 27 ].…”
Section: No and Schizophreniamentioning
confidence: 99%
“…Several reports have targeted the levels of cerebral and peripheral PA in schizophrenia patients. Elevated blood concentrations of spermine and/or spermidine have been measured in treated schizophrenia patients[ 73 , 74 ] and in drug-naïve cases[ 75 ], whereby long-term neuroleptic treatment was shown to reduce spermine levels[ 75 , 76 ]. Also, increased concentrations of spermidine and total PA were detected in fibroblasts obtained from schizophrenia patients (reviewed in[ 11 ]).…”
Section: Pa Content In Tissues and Body Fluids In Schizophreniamentioning
confidence: 99%
“…Curiously, the opposite is the case as either increased blood and brain levels[ 73 - 75 ] or normal concentrations[ 65 ] of PA and ODC[ 81 , 85 , 87 ] have been reported for schizophrenia and animal disease models. Moreover, increased PA levels are not the result of neuroleptic treatment since anti-psychotics decrease PA concentrations in tissues and blood[ 75 , 76 ]. Thus, it seems unlikely that increased concentrations of spermine or other PAs contribute to schizophrenia pathology.…”
Section: Possible Impact Of Pa Pathway Abnormalities On Schizophrenia Pathologymentioning
confidence: 99%
“…Several genes involved in polyamine metabolism have been shown to be altered in patients with schizophrenia 107,108 . Assessment and comparison of polyamine levels in psychiatric patients with schizophrenia and healthy controls have shown a significant increase in the concentration of polyamine oxidative enzymes in the blood of schizophrenic patients, 107,109–111 whereas results from skin fibroblast studies showed that polyamines were increased in antipsychotic‐treated patients, as compared to drug‐free patients 112 . In the human frontal cortex and hippocampus, no alteration was found in polyamines and ODC activity between patients with schizophrenia and healthy controls 113 .…”
Section: The Endogenous Antagonists Of the Nmdar In Schizophreniamentioning
confidence: 99%